Hygroscopic and microstructural analyses of dehydrated fruits - Borges, Soraia V.; Cal-Vidal, José (Pesquisa Agropecuaria Brasileira, 1994)
The hygroscopic behavior of dehydrated fruits (Carica papaya, Mangifera indica and Musa sp) was analysed based on the isotherm and kinetics of water sorption at several environmental conditions of temperature (10, 20 and 40°C) and relative humidity (33 to 87%). The chemical composition and microstructure were also searched. The results showed an influence of the sugars on the equilibrium moisture. This products presented a porous structure, and the water sorption rate for banana and mango was influenced by the amount of water absorbed and by the environmental conditions (temperature and relative humidity).